EVALUASI PROGRAM MUSYAWARAH GURU BIMBINGAN DAN KONSELING SMP/MTS KOTA SALATIGA TAHUN 2012 â 2015 - Onate, Maria Evangeli; Loekmono, Ph.D, Prof. J.T Lobby (Kelola: Jurnal Manajemen Pendidikan, 2016)
This study aimed to evaluate the context, input, process, and product of Guidance and Counseling Teachers Deliberation Program (MGBK) at SMP / MTs Salatiga year of 2012-2015. This study was evaluation research using CIPP model (Context, Input, Process, Product) developed by Stufflebeam. Data collection techniques used in this study were interviews, observation, study of documentation and FGD (focus group discussion). The validity test used data triangulation. The results of this study showed that 1) the context evaluation of the objective set by MGBK program was in the unfavorable category, while the analysis of the needs was in the sufficient category; 2) the inputÂ  evaluation indicated that the human resources namely committee and speakers of MGBK was in the very good category, while the MGBK members was in the good category. Furthermore, sources of funding and supporting infrastructure of MGBK program implementation was in the good categoriy; 3) the process evaluation was in the sufficient category although not all the programmed activities can be implemented; 4) theÂ  product of the implementation of the MGBK program was in the sufficient category.